PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM MULTIKULTURAL: TINJAUAN LITERATUR - Nurbaya, Siti; Tang, Muhammad; Palili, Sampara (Fitrah, 2024)
This writing aims to analyze the theories and principles of developing a multicultural Islamic Religious Education curriculum. The study employs a literature review method with a qualitative approach to understand the principles of curriculum development. Data sources include books, journals, research findings, and relevant theses, which are analyzed using content analysis techniques to sort, identify, and summarize information from various literature to provide a different perspective on the multicultural Islamic Religious Education curriculum. The study's findings reveal that the development of a multicultural Islamic Religious Education curriculum is based on two main principles: general and specific principles. The general principles emphasize Islamic values and cultural diversity as learning resources while preserving cultural heritage. The specific principles cover aspects such as objectives, content, processes, facilities, and curriculum assessment. Both principles are designed to create a flexible and comprehensive curriculum that fosters tolerance and appreciation for pluralism. This curriculum is expected to facilitate inclusive and relevant learning that meets the needs of multicultural societies, thereby promoting social harmony and cultural awareness.